2021
DOI: 10.1039/d1ra01147b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of indazole derivatives as anti-cancer agents

Abstract: One of the synthesized indazole derivatives, 2f, displayed inhibitory activities against proliferation, migration and invasion of breast cancer cell line 4T1, with the potential of inducing cell apoptosis, and suppressing tumor growth in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…A (pyridine‐2‐yl)piperazine clubbed with indazole derivative ( 191 ) had shown excellent in‐vitro antiproliferative activity against 4T1 (mouse breast cancer) and MCF‐7 cell line with IC 50 values of 0.23 and 0.34 µM, respectively. Wei et al (2021) suggested that compound 191 (Figure 20) might induce mitochondrial apoptotic pathway via caspase‐3 dependent manner using annexin V‐FITC/PI flow cytometry assay and western blot analysis. In 4T1‐tumor‐bearing female BalB/c mice, it was tested in‐vivo for anticancer activity at doses of 12.5 and 25 mg/kg once a day, which suggested dose‐dependent suppression of tumor volume with no obvious and remarkable side effect (Wei et al, 2021).…”
Section: Anticancer Activities Of Some Indazole Derivatives: Recent U...mentioning
confidence: 99%
See 3 more Smart Citations
“…A (pyridine‐2‐yl)piperazine clubbed with indazole derivative ( 191 ) had shown excellent in‐vitro antiproliferative activity against 4T1 (mouse breast cancer) and MCF‐7 cell line with IC 50 values of 0.23 and 0.34 µM, respectively. Wei et al (2021) suggested that compound 191 (Figure 20) might induce mitochondrial apoptotic pathway via caspase‐3 dependent manner using annexin V‐FITC/PI flow cytometry assay and western blot analysis. In 4T1‐tumor‐bearing female BalB/c mice, it was tested in‐vivo for anticancer activity at doses of 12.5 and 25 mg/kg once a day, which suggested dose‐dependent suppression of tumor volume with no obvious and remarkable side effect (Wei et al, 2021).…”
Section: Anticancer Activities Of Some Indazole Derivatives: Recent U...mentioning
confidence: 99%
“…Wei et al (2021) suggested that compound 191 (Figure 20) might induce mitochondrial apoptotic pathway via caspase‐3 dependent manner using annexin V‐FITC/PI flow cytometry assay and western blot analysis. In 4T1‐tumor‐bearing female BalB/c mice, it was tested in‐vivo for anticancer activity at doses of 12.5 and 25 mg/kg once a day, which suggested dose‐dependent suppression of tumor volume with no obvious and remarkable side effect (Wei et al, 2021).…”
Section: Anticancer Activities Of Some Indazole Derivatives: Recent U...mentioning
confidence: 99%
See 2 more Smart Citations
“…A search in different databases shows that the chemistry of indazoles is a very active field; the numbers of items are 11 723 (Scifinder), 5142 (ScienceDirect), and 4448 (Web of Science); and most of the papers and patents deal with biological applications. Other applications (corrosion inhibitors) and synthetic methods are less reported, and the last place is occupied by indazole reactivity.…”
Section: Introductionmentioning
confidence: 99%